(untitled) (Veterinary Science, 2022)
Biokinematic variables of the locomotion of the Criollo Argentino breed of horses, of which there is no specific information. These variables may be used with clinical and physiotherapeutic objectives and in reproduction programmes. 8 Criollo Argentino mares were used in the study. Refractive markers were placed in anatomical sites previously determined. They were made to trot covering a distance of 15 meters on grass guided by hand. Each individual repeated the activity three times, which were recorded on video. The photograms were introduced in the software ImageJ to measure the joint angles of scapular and pelvic inclination, protraction, retraction, extension, flexion and angular amplitude of each joint in the limbs. Simultaneously, the length and number of strides for all limbs and the speed at which they covered 15 meters. The statistical description of variables was carried out. The horses covered the distance in 22.99 sec. at 4.08 m/sec. doing 5.69 strides of a length of 2.66 m. per 0.65 sec.. The protraction and retraction angles were 22.63º and 6.8º; 9.06º and 22.03º for the thoracic and pelvic limbs. The scapular and pelvic inclination angles were 73.19º-60.79º (12.4º); and 33.11º-26.52º (6,58º). The extension and flexion angles and angular amplitude were: shoulder 12807º-116.93º, 11.13º, elbow 159.85º-144.60º, 15.52º; carpus 175.85º-172.18º, 3.66º, hip 103.38º–86.19º, 17.18º; patella 138.57º-118.56º, 20.01º; tarsus 153.79º–142.85º, 10.94º and thoracic limb fetlock 159.68º-126.89º, 32.79º and pelvic limb fetlock 161.09º-129.68º, 31.41º. The range of retraction-protraction of the limbs contributes to the knowledge of synchronicity of the ipsilateral retraction of the forelimb and the protraction of the hindlimb during trotting. The Criollo Argentino’s performance at trot requires the synchronization of joint extension and flexion whose minimal and maximum variations were registered.